A heat-resistant and flame-retardant PVC material and preparation method thereof
By using PTFE-based anti-drip agent and calcium-zinc composite stabilizer in PVC materials, combined with quaternized modified glass microbeads, the problem of melting droplets when softening and burning at high temperatures is solved, and higher heat resistance and flame retardant properties are achieved.
Patent Information
- Application Number
- CN202411461491.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-10-18
AI Technical Summary
PVC materials are prone to softening, deforming or thermal decomposition in high temperature environments, and the melting droplet phenomenon during combustion may aggravate the spread of fires, affecting safety and application potential.
Using an anti-drip agent based on PTFE material, by introducing imidazole rings and epoxy groups into the shell of the anti-drip agent, combining quaternized modified glass microbeads, a three-dimensional network structure is formed to prevent the formation of melt droplets, and a calcium-zinc composite stabilizer is used to improve thermal stability.
It significantly improves the heat resistance and flame retardant properties of PVC materials, inhibits the droplet phenomenon, and enhances the mechanical strength and safety of the materials.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the field of polyvinyl chloride materials, and in particular to a heat-resistant and flame-retardant PVC material and a preparation method thereof. Background Art
[0002] As a widely used thermoplastic, polyvinyl chloride (PVC) has shown significant advantages in industries such as construction, packaging, wire and cable insulation, automotive interiors and parts due to its good processability, corrosion resistance, cost-effectiveness and relatively light weight.
[0003] Compared with other plastics, PVC material has obvious advantages in flame retardancy, which is reflected in the ability to produce hydrogen chloride gas when it initially contacts the fire source, slowing down the spread of flames. However, its insufficient heat resistance limits its application potential. In high temperature environments, PVC materials are prone to softening, deformation, and even thermal decomposition, which not only weakens the mechanical properties and structural integrity of the material, but may also cause more serious safety problems. It is particularly important to note that PVC will be accompanied by melt dripping during the combustion process. If these high-temperature melts cannot be effectively controlled, they can easily become a medium for the spread of fire, especially when they come into contact with combustible materials in the surrounding environment. This will increase the speed and scope of the spread of the fire, posing a major threat to personal safety and property. Summary of the invention
[0004] In order to alleviate the poor heat resistance of current PVC materials and the dripping phenomenon during combustion, the present application provides a heat-resistant and flame-retardant PVC material and a preparation method thereof.
[0005] In a first aspect, the present application provides a heat-resistant and flame-retardant PVC material, which comprises the following raw materials in parts by weight:
[0006] 100 parts of PVC resin, 5-15 parts of heat-resistant filler, 1-3 parts of calcium-zinc composite stabilizer, 1-5 parts of plasticizer, 2-5 parts of anti-dripping agent, 0.5-2 parts of lubricant;
[0007] The anti-dripping agent has a core-shell structure. The core layer raw material of the anti-dripping agent includes PTFE emulsion; the shell layer raw material includes 10-20 parts of styrene, 5-10 parts of vinylidene chloride; 0.1-1.5 parts of initiator; the mass ratio of PTFE powder to vinylidene chloride in the PTFE emulsion is 10-20:5-10.
[0008] Preferably, the calcium-zinc composite stabilizer is a composition of calcium stearate and zinc stearate; more preferably, the mass ratio of calcium stearate to zinc stearate is 1-1.2:1-1.2.
[0009] Preferably, the plasticizer is a polyester plasticizer.
[0010] Preferably, the lubricant is one or more of monoglyceride, polyethylene wax, oxidized polyethylene wax, montan wax, polyester wax and paraffin wax.
[0011] In order to suppress the melting and dripping phenomenon of PVC during combustion, the present application adopts an anti-dripping agent based on PTFE material, which can quickly fiberize when the polyamide material burns, forming a three-dimensional network structure, preventing the melting and dripping of the polyamide material, and effectively suppressing the formation of molten droplets, thereby improving its flame retardant effect. It should be noted that due to the poor compatibility of the shell polymer of the traditional anti-dripping agent with the polyvinyl chloride resin, the anti-dripping agent is difficult to disperse and has a tendency to agglomerate. In the preparation of the shell polymer, the present application adds vinylidene chloride monomer, which effectively improves the affinity of the anti-dripping agent with the PVC resin, and helps to improve the flame retardant properties of the PVC material. In addition, the heat-resistant filler has good high temperature resistance, and the heat resistance of the PVC resin can be significantly improved after blending and modification.
[0012] Preferably, the raw material of the shell layer further comprises 1 to 4 parts of an imidazole compound having an unsaturated double bond.
[0013] Preferably, the imidazole compound having an unsaturated double bond is allyl imidazole and / or vinyl imidazole.
[0014] Heat stabilizers are key additives to prevent PVC from degrading during high-temperature processing. Several commonly used heat stabilizers include lead salts, barium-cadmium, organic tin, and calcium-zinc composite stabilizers. Among them, lead salts and barium-cadmium are gradually eliminated due to environmental and safety performance issues; organic tin has outstanding effects but poor lubricity and economic performance. Therefore, calcium-zinc composite stabilizers that are non-toxic, environmentally friendly, economical, and have outstanding lubricity are the mainstream choice. Its mechanism of action is to replace the active chlorine atoms in the PVC molecular chain and absorb the hydrogen chloride (HCl) produced during the high-temperature processing of PVC, inhibiting the catalytic degradation of hydrogen chloride. However, in the above-mentioned process, zinc stearate generates Lewis acid (zinc chloride) with catalytic dehydrogenation, which accelerates the degradation of PVC and is not conducive to improving the mechanical strength of PVC materials.
[0015] Based on the above problems, the present application adopts an imidazole compound with an unsaturated double bond, introduces an imidazole ring into the shell of the anti-dripping agent, utilizes its coordination and complexing effect on metal ions, absorbs and fixes zinc chloride, inhibits the discoloration caused by the catalytic degradation of zinc chloride, improves the thermal stability of the PVC material, and ensures the mechanical strength of the PVC material.
[0016] Preferably, the heat-resistant filler is quaternized modified glass microspheres, which are prepared by sequentially reacting glass microspheres with an aminosilane coupling agent and 2,3-epoxypropyltrimethylammonium chloride.
[0017] Preferably, the mass ratio of the glass microspheres to the aminosilane coupling agent is 100:2-5, and the molar ratio of the amino group to 2,3-epoxypropyltrimethylammonium chloride in the aminosilane coupling agent is 1:0.6-0.8.
[0018] Preferably, the aminosilane coupling agent includes at least one of γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, γ-aminopropylmethyldimethoxysilane, γ-aminopropylmethyldiethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and N-(β-aminoethyl)-γ-aminopropyltriethoxysilane.
[0019] Preferably, the D50 particle size of the glass microspheres is 1 to 50 microns, more preferably 5 to 10 microns.
[0020] Compared with fillers such as calcium carbonate, glass microspheres contain alkali metal oxides, which can neutralize and absorb HCl released during the thermal decomposition of PVC, thereby improving the thermal stability of PVC. In addition, glass microspheres have the characteristics of low friction resistance and high thermal lubricity, and are not easy to reduce the melt extrusion performance. Through quaternization modification, the tendency of agglomeration can be suppressed through steric hindrance and electrostatic effects, and its full dispersion can be promoted to ensure the improvement of the heat resistance of PVC materials, and it can also play a certain antibacterial and mildew-proof role.
[0021] Preferably, the raw material of the shell layer further comprises 3 to 5 parts of epoxy-containing comonomer.
[0022] Preferably, the epoxy-containing comonomer includes at least one of glycidyl methacrylate, glycidyl acrylate, allyl glycidyl ether, and bismaleimido methacrylate.
[0023] Introducing epoxy groups on the surface of the anti-dripping agent allows it to react and bond with the amino groups on the surface of the heat-resistant filler, thereby adsorbing a small amount of quaternary ammonium modified glass microspheres to form a heat-resistant layer, which is beneficial to enhancing the thermal stability of the anti-dripping agent. In addition, during high-temperature processing such as melt blending, the unexpected fiberization of the anti-dripping agent caused by high temperature and mechanical stirring is reduced, which is beneficial to ensuring the flame retardant properties and mechanical strength of PVC.
[0024] It should be noted that in order to ensure the reaction and bonding between the anti-dripping agent and the heat-resistant filler, the molar ratio of the epoxy group to the amino group must be controlled during the quaternization modification process to ensure that an appropriate amount of amino reaction sites are left on the surface of the heat-resistant filler.
[0025] Preferably, the preparation method of the anti-dripping agent is as follows:
[0026] Emulsification: Add PTFE powder and emulsifier into water for ultrasonic dispersion to prepare PTFE emulsion;
[0027] Copolymerization: add shell material to PTFE emulsion under stirring condition, stir evenly, heat to 65-75°C for free radical copolymerization, obtain copolymerization product after the reaction is completed, filter out the material, condense, wash and dry.
[0028] Preferably, the emulsifier is selected from nonionic surfactants; more preferably fatty alcohol polyoxyethylene ether or fatty acid polyoxyethylene ester.
[0029] Preferably, the initiator is selected from one or more of azobisisobutyronitrile, azobisisoheptanenitrile and dimethyl azobisisobutyrate, ammonium persulfate, potassium persulfate, ammonium persulfate, benzoyl peroxide, tert-butyl benzoyl peroxide, and methyl ethyl ketone peroxide.
[0030] In a second aspect, the present application provides a method for preparing a heat-resistant and flame-retardant PVC material, which comprises the following steps:
[0031] According to the raw material ratio of any of the above-mentioned PVC materials, weigh PVC resin, plasticizer, heat-resistant filler, calcium-zinc composite stabilizer, anti-dripping agent, and lubricant, add them into a mixer, heat up to 110-130° C. and mix evenly;
[0032] The uniformly mixed blend is introduced into a twin-screw extruder for melt extrusion granulation to obtain a heat-resistant and flame-retardant PVC material.
[0033] In summary, this application has the following beneficial effects:
[0034] The present invention discloses the preparation of an anti-dripping agent with good compatibility with PVC resin, which can give PVC materials good anti-melting dripping performance and improve their flame retardancy. Furthermore, the present application introduces imidazole rings on the surface of the anti-dripping agent, which can complex and adsorb the Lewis acid product of the calcium-zinc composite stabilizer, thereby inhibiting its catalytic degradation effect on PVC molecules and improving the thermal stability of PVC resin during high-temperature processing. In addition, the present application introduces epoxy groups on the surface of the anti-dripping agent, combined with the amino groups on the surface of the quaternary ammonium-modified glass microspheres, to prevent the probability of unexpected fiberization of the anti-dripping agent during the blending process, thereby ensuring the mechanical properties of the material. DETAILED DESCRIPTION
[0035] Preparation Example 1-1, an anti-dripping agent, is prepared according to the following steps:
[0036] Mixing: Add Span 60 into deionized water to prepare an emulsifier solution with a concentration of 2wt%, then add 1.5kg PTFE powder (DuPont 301 powder), ultrasonically disperse for 1h, and prepare a PTFE emulsion for use.
[0037] Copolymerization: Under the stirring condition of 1000rpm, add 1.6kg styrene, 0.6kg vinylidene chloride, 0.25kg 1-allylimidazole, 0.4kg glycidyl methacrylate to the PTFE emulsion, stir evenly, then add 0.04kg benzoyl peroxide, raise the temperature to 68°C, keep warm for 4h to carry out polymerization reaction, and obtain the copolymer product after the reaction is completed. Filter the material, condense, wash with deionized water and dry.
[0038] Preparation Example 1-2, an anti-dripping agent, is prepared according to the following steps:
[0039] Mixing: Add Span 60 into deionized water to prepare an emulsifier solution with a concentration of 2wt%, then add 1kg PTFE powder (DuPont 301 powder), ultrasonically disperse for 1h, and prepare a PTFE emulsion for use.
[0040] Copolymerization: Under the stirring condition of 1000rpm, add 1.1kg styrene, 0.5kg vinylidene chloride, 0.15kg 1-allylimidazole, 0.3kg allyl glycidyl ether to the PTFE emulsion, stir evenly, then add 0.02kg benzoyl peroxide, raise the temperature to 72℃, keep warm for 4h to carry out polymerization reaction, and obtain the copolymer product after the reaction is completed. Filter the material, condense, wash with deionized water and dry.
[0041] Preparation Example 1-3, anti-dripping agent, is prepared according to the following steps:
[0042] Mixing: Add Span 60 into deionized water to prepare an emulsifier solution with a concentration of 2wt%, then add 2kg PTFE powder (DuPont 301 powder), ultrasonically disperse for 1h, and prepare a PTFE emulsion for use.
[0043] Copolymerization: Under the stirring condition of 800rpm, add 2kg styrene, 0.95kg vinylidene chloride, 0.4kg 1-vinylimidazole, 0.45kg glycidyl methacrylate to the PTFE emulsion, stir evenly, then add 0.05kg benzoyl peroxide, raise the temperature to 70℃, keep warm for 5h to carry out polymerization reaction, and obtain the copolymer product after the reaction is completed. Filter the material, condense, wash with deionized water and dry.
[0044] Preparation Example 1-4, an anti-dripping agent, is different from Preparation Example 1-1 in that 1-allylimidazole is replaced by an equal amount of styrene.
[0045] Preparation Example 1-5, an anti-dripping agent, is different from Preparation Example 1-1 in that glycidyl methacrylate is replaced by an equal amount of styrene.
[0046] Preparation Example 1-6, an anti-dripping agent, is different from Preparation Example 1-1 in that vinylidene chloride is replaced by an equal amount of styrene.
[0047] Preparation Example 2-1, heat-resistant filler, is prepared according to the following method:
[0048] 100 g of glass microspheres (D50 particle size: 10 μm) were added to 500 ml of a mixture of ethanol and water (ethanol 90 wt%), and 4.1 g of aminopropyltriethoxysilane was added. The mixture was stirred for 30 min, the product was filtered out, washed three times with deionized water, and dried to constant weight to obtain amino-modified glass microspheres.
[0049] The obtained amino-modified glass microspheres and 2 g of 2,3-epoxypropyltrimethylammonium chloride were added to an isopropanol solution, uniformly dispersed, heated to 70°C, and stirred for reaction for 16 hours. After the reaction was completed, the product was separated, washed three times with deionized water, and dried at 45°C to constant weight to obtain a heat-resistant filler.
[0050] Preparation Example 2-2, heat-resistant filler, is prepared according to the following method:
[0051] 100 g of glass microspheres (D50 particle size: 5 μm) were added to 500 ml of a mixture of ethanol and water (ethanol 90 wt%), and 2.3 g of aminopropyltrimethoxysilane was added. The mixture was stirred for 30 min, the product was filtered out, washed three times with deionized water, and dried to constant weight to obtain amino-modified glass microspheres.
[0052] The obtained amino-modified glass microspheres and 1.5 g of 2,3-epoxypropyltrimethylammonium chloride were added to an isopropanol solution, uniformly dispersed, heated to 78°C, and stirred for reaction for 12 hours. After the reaction was completed, the product was separated, washed three times with deionized water, and dried at 45°C to constant weight to obtain a heat-resistant filler.
[0053] Preparation Example 2-3, heat-resistant filler, is prepared according to the following method:
[0054] 100 g of glass microspheres (D50 particle size: 10 μm) were added to 500 ml of a mixture of ethanol and water (ethanol 90 wt%), and 5.0 g of aminopropyltrimethoxysilane was added. The mixture was stirred for 1 h, the product was filtered out, washed three times with deionized water, and dried to constant weight to obtain amino-modified glass microspheres.
[0055] The obtained amino-modified glass microspheres and 2.5 g of 2,3-epoxypropyltrimethylammonium chloride were added to an isopropanol solution, uniformly dispersed, heated to 60°C, and stirred for reaction for 24 hours. After the reaction was completed, the product was separated, washed three times with deionized water, and dried at 45°C to constant weight to obtain a heat-resistant filler.
[0056] Preparation Example 2-4, heat-resistant filler, is prepared according to the following method:
[0057] Add 100 g of glass microbeads (D50 particle size: 10 μm) to 500 ml of a mixture of ethanol and water (ethanol 90 wt%), add 5.0 g of vinyltrimethoxysilane, stir and react for 1 h, filter out the product, wash three times with deionized water, and dry to constant weight. Example
[0058] The raw materials selected in the embodiment are as follows: the plasticizer is adipic acid polyester plasticizer ADK CIZER PN-400; the calcium zinc composite stabilizer is purchased from Hangzhou Lianbo New Materials; and the lubricant is polyethylene wax.
[0059] Example 1, a heat-resistant and flame-retardant PVC material is prepared according to the following steps:
[0060] Weigh 10kg SG-5 type PVC resin, 0.33kg plasticizer (ADK CIZER PN-400), 1kg heat-resistant filler of Preparation Example 2-1, 0.18kg calcium zinc composite stabilizer, 0.36kg anti-dripping agent of Preparation Example 1-1, and 0.1kg lubricant, add to a high-speed mixer, heat to 120°C and mix for 15 minutes, then enter into a cooling mixer, and when the temperature reaches 50°C, cool and discharge to obtain a blend.
[0061] The blended material is passed into a twin-screw extruder for melt extrusion, cooling and granulation. The temperatures of the screw sections are set to 150°C, 165°C, 175°C, 190°C, 185°C and 170°C in sequence.
[0062] Example 2, a heat-resistant and flame-retardant PVC material is prepared according to the following steps:
[0063] Weigh 10kg SG-5 type PVC resin, 0.16kg plasticizer (ADK CIZER PN-400), 0.55kg heat-resistant filler of Preparation Example 2-2, 0.3kg calcium zinc composite stabilizer, 0.5kg anti-dripping agent of Preparation Example 1-2, and 0.2kg lubricant, add into a high-speed mixer, heat to 120°C and mix for 15 minutes, then enter into a cooling mixer, and when the temperature reaches 40°C, cool and discharge to obtain a blend.
[0064] The blended material is passed into a twin-screw extruder for melt extrusion, cooling and granulation. The temperatures of the screw sections are set in sequence as follows: 160°C, 170°C, 175°C, 185°C, 185°C and 175°C.
[0065] Example 3, a heat-resistant and flame-retardant PVC material is prepared according to the following steps:
[0066] Weigh 10kg SG-5 type PVC resin, 0.5kg plasticizer (ADK CIZER PN-400), 1.45kg heat-resistant filler of Preparation Example 2-3, 0.12kg calcium zinc composite stabilizer, 0.23kg anti-dripping agent of Preparation Example 1-3, and 0.05kg lubricant, add into a high-speed mixer, heat to 120°C and mix for 15 minutes, then enter into a cooling mixer, and when the temperature reaches 50°C, cool and discharge to obtain a blend.
[0067] The blended material is passed into a twin-screw extruder for melt extrusion, cooling and granulation. The temperatures of the screw sections are set in sequence as follows: 160°C, 175°C, 180°C, 190°C, 180°C and 165°C.
[0068] Example 4, a heat-resistant and flame-retardant PVC material, is different from Example 1 in that the anti-dripping agent of Preparation Example 1-1 is replaced by an equal amount of the anti-dripping agent of Preparation Example 1-4.
[0069] Example 5, a heat-resistant and flame-retardant PVC material, is different from Example 1 in that the anti-dripping agent of Preparation Example 1-1 is replaced by an equal amount of the anti-dripping agent of Preparation Example 1-5.
[0070] Example 6, a heat-resistant and flame-retardant PVC material, is different from Example 1 in that the heat-resistant filler of Preparation Example 2-1 is replaced by an equal amount of the heat-resistant filler of Preparation Example 2-4. Comparative Example
[0071] Comparative Example 1, a heat-resistant and flame-retardant PVC material, is different from Example 6 in that the anti-dripping agent of Preparation Example 1-1 is replaced by an equal amount of the anti-dripping agent of Preparation Example 1-6.
[0072] Comparative Example 2, a heat-resistant and flame-retardant PVC material, is different from Example 6 in that the anti-dripping agent of Preparation Example 1-1 is replaced by an equal amount of commercially available Mitsubishi A-3800 anti-dripping agent.
[0073] Performance testing
[0074] 1. Flame retardant performance: Determined in accordance with the test requirements of the vertical burning test in UL94.
[0075] 2. Tensile strength: Test in accordance with the requirements of GB / T1040-1992 "Test method for tensile properties of plastics".
[0076] 3. Heat resistance: Test according to the requirements of GB / T 15595-2008 "Test method for thermal stability of polyvinyl chloride resin - Whiteness method".
[0077] Table 1. Performance test results
[0078]
[0079] It can be seen from the test results in Table 1 that the embodiment has more superior flame retardant properties than the comparative example. The reason may be that the anti-dripping agent added in the present application has good compatibility with the PVC resin, which can significantly improve the inhibition of the dripping phenomenon during the combustion process, and combined with the self-extinguishing effect of PVC itself, it can achieve a flame retardant effect of V-0 grade.
[0080] From the test results in Table 1, it can be seen that Example 1 has more outstanding heat resistance than Example 4. The reason may be that the anti-dripping agent used in Example 1 has an imidazole ring structure introduced on the surface, which can complex and adsorb zinc chloride produced by the calcium zinc heat stabilizer during processing, thereby reducing its thermal degradation of PVC molecules, reducing the yellowing and blackening phenomenon of PVC, and ensuring its mechanical strength.
[0081] It can be seen from the test results in Table 1 that Example 1 has higher mechanical strength than Examples 5 and 6. The reason may be that epoxy groups are introduced on the surface of the anti-dripping agent of Example 1, which can bond with the quaternary ammonium modified glass microspheres through a ring-opening reaction, thereby forming a protective layer on the surface of the anti-dripping agent, reducing the mechanical action of the processing process and the unexpected fiberization caused by high temperature, and preventing the PTFE component therein from reducing the mechanical properties of the PVC material.
[0082] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A heat-resistant and flame-retardant PVC material, characterized in that: The invention comprises the following raw materials in parts by weight: 100 parts of PVC resin, 5-15 parts of heat-resistant filler, 1-3 parts of calcium-zinc composite stabilizer, 1-5 parts of plasticizer, 2-5 parts of anti-dripping agent, 0.5-2 parts of lubricant; The anti-dripping agent has a core-shell structure, the core layer raw material of the anti-dripping agent includes PTFE emulsion; the shell layer raw material includes 10-20 parts of styrene, 5-10 parts of vinylidene chloride; 0.1-1.5 parts of initiator; the mass ratio of PTFE powder to vinylidene chloride in the PTFE emulsion is 10-20:5-10; The heat-resistant filler is quaternized modified glass microspheres, which are prepared by sequentially reacting glass microspheres with an aminosilane coupling agent and 2,3-epoxypropyltrimethylammonium chloride; the mass ratio of the glass microspheres to the aminosilane coupling agent is 100:2-5, and the molar ratio of the amino group in the aminosilane coupling agent to the 2,3-epoxypropyltrimethylammonium chloride is 1:0.6-0.
8.
2. The PVC material according to claim 1, characterized in that: The raw materials of the shell layer also include 1 to 4 parts of an imidazole compound having an unsaturated double bond.
3. The PVC material according to claim 2, characterized in that: The imidazole compound having an unsaturated double bond is allyl imidazole and / or vinyl imidazole.
4. The PVC material according to claim 1, characterized in that: The aminosilane coupling agent includes at least one of γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, γ-aminopropylmethyldimethoxysilane, γ-aminopropylmethyldiethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and N-(β-aminoethyl)-γ-aminopropyltriethoxysilane.
5. The PVC material according to claim 1, characterized in that: The raw materials of the shell layer also include 3 to 5 parts of epoxy-containing comonomers.
6. The PVC material according to claim 5, characterized in that: The epoxy-containing comonomer includes at least one of glycidyl methacrylate, glycidyl acrylate, allyl glycidyl ether, and bismaleimide methacrylate.
7. The PVC material according to claim 1, characterized in that: The preparation method of the anti-dripping agent is as follows: Emulsification: Add PTFE powder and emulsifier into water for ultrasonic dispersion to prepare PTFE emulsion; Copolymerization: add shell material to PTFE emulsion under stirring condition, stir evenly, heat to 65-75°C for free radical copolymerization, obtain copolymerization product after the reaction is completed, filter out the material, condense, wash and dry.
8. A method for preparing a heat-resistant and flame-retardant PVC material, characterized in that: The steps include: According to the raw material ratio described in any one of claims 1 to 7, weigh PVC resin, plasticizer, heat-resistant filler, calcium-zinc composite stabilizer, anti-dripping agent, and lubricant, add them into a mixer, heat up to 110-130° C. and mix evenly; The uniformly mixed blend is introduced into a twin-screw extruder for melt extrusion granulation to obtain a heat-resistant and flame-retardant PVC material.
Citation Information
Patent Citations
Hollow glass bead / polyvinyl chloride component type wire and cable compound and preparation method thereof
CN103923411A
Cable material and preparation method thereof
CN111909470A
Cited By
Preparation method of high-strength flame-retardant PVC (Polyvinyl Chloride) based on modification of MOS (Metal Oxide Semiconductor) whiskers SiO2-CNT (Carbon Nanotube) composite filler
CN121362408A